An approach to the implementation of Low Impact Development measures towards an EcoCampus classification. (15th February 2019) - Matos, C.; Briga Sá, A.; Bentes, I.; Pereira, S.; Bento, R.
Abstract: Impervious cover has important hydrologic impacts, namely the increased runoff volume and peak discharges in the rainwater network, which can lead to significant consequences like rapid urban floods with social, environmental and economic implications. LID (Low Impact Development) consist of distributed runoff management measures, like green roofs, pervious pavements, waterways covered with vegetation and filter trails, among others, that seek to control stormwater in the origin, reducing imperviousness. These solutions avoid increased runoff rate and volume, increase infiltration and groundwater recharge. The main goal of the research work here presented is to study the hydrological impact of LID's in UTAD (University of Trás-os-Montes e Alto Douro) campus, which is an institution focused on sustainability, since it has defined in its Strategic Plan to achieve, in a near future, an EcoCampus classification. To achieve the proposed goal, the campus area was studied in detail in order to evaluate the technical possibility of LID's implementation. A peak discharge comparison was made between the current situation and the one with LID's implementation, using the rational method. The results showed that peak discharges reduction between 68 and 95% may be achieved with LID solutions in UTAD campus. Highlights: UTAD campus is an institution foccused to achieve the Ecocampus classification. Peak discharge comparison was made between the current situation and the one with LID's. Peak discharges reductions between 68 and 95% may be achieved with LID.